2014
DOI: 10.1007/s00330-014-3424-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area measurements versus volumetric assessment of the quadriceps femoris muscle in patients with anterior cruciate ligament reconstructions

Abstract: • Cross-sectional area was used to estimate QFM size in patients with ACL-reconstruction • A high correlation coefficient exists between quadriceps CSA and volume • Best correlation was seen 25 cm above the knee joint line • A relatively large standard error of the estimate limits CSA application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…The CI did not cross zero in the study demonstrating a large, negative effect size. The study with the small, negative effect size and the study with the moderate, negative effect size had CIs that crossed zero, indicating there was not a meaningful difference between limbs.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The CI did not cross zero in the study demonstrating a large, negative effect size. The study with the small, negative effect size and the study with the moderate, negative effect size had CIs that crossed zero, indicating there was not a meaningful difference between limbs.…”
Section: Resultsmentioning
confidence: 96%
“…Three studies assessed quadriceps CSA after ACLR . Of these three studies, one demonstrated a large, negative effect size, one demonstrated a moderate, negative effect size, and one demonstrated a small, negative effect size .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10] The CSA measurement may not be representative of muscle volume, depending on the level of estimation along the muscle's length, and can be affected by the shape of the muscles. 11,12 As the lumbar conically shaped multifidus crosses 3 or more vertebral segments, measurement of the CSA using conventional magnetic resonance imaging (MRI) may be inadequate to predict the morphology or integrity of the entire muscle.…”
mentioning
confidence: 99%